The Invisible Palestinians : The Hidden Struggle for Inclusion in Jewish Tel Aviv - Hackl, Andreas (Book collections on Project MUSE., 2022)
"Within the heart of the Jewish city of Tel Aviv, there is a hidden reality-Palestinians who work, study, and live as an unseen minority without access to equal urban citizenship. Grounded in the everyday lives of Palestinians in Tel Aviv, The Invisible Palestinians offers an ethnographic critique of the city's self-proclaimed openness and liberalism. Andreas Hackl reveals that Palestinians' access to the social and economic opportunities afforded in Tel Aviv depends on an invisibility that not only disrupts opportunities for true urban citizenship but also draws opposition from other Palestinians. They are unable to belong in Tel Aviv as Palestinians and struggle to reconcile Tel Aviv with being Palestinian. By looking at the city from the perspective of this hidden urban minority, Hackl uncovers a critical opportunity to imagine and build a more inclusive and just future for Tel Aviv. An important read, The Invisible Palestinians explores the marginalized urban presence of both Palestinian citizens of Israel and Palestinian labourers from the West Bank in this quintessential Jewish Israeli city. Andreas reveals a highly diverse Palestinian population that includes young people, manual workers and middle class professionals, residents and commuters, students, artists, and activists, as well as members of an underground Palestinian LGBT community that carefully navigates their place in a city that refuses to recognize them"--